PEMECAHAN MASALAH POLYA DARI SISWA SMP BERGAYA KOGNITIF FIELD DEPENDENT DAN FIELD-INDEPENDENT - Eva, Rusmala (Universitas Negeri Surabaya, 2019)
The aim of this research is to describe the profile of student's problem solving in the Pythagoras Theorem problem based on the cognitive styles of FI and FD. The subjects of this research consisting of 2 subjects FI and 2 subjects FD class VIII H SMP Negeri 2 Lumajang. Instruments used: cognitive style tests (GEFT), Pythagoras Theorem problem solving tests, and interview guideline. Problem-solving indicators that be used is Polya's problem solving steps: understanding the problem, devise a plan, carry out the plan, and looking back. The results of this study is the FI subject is better than the FD subject. The FI subject understand the problem very well, arranging a solution plan well, implementing a plan properly, looking back well,make error but not any step. Nevertheless, The FD subjects are categorized as lacking in the step of understanding the problem, devising a plan with deficient category, implementing the plan without looking back on the solution, so it is categorized as lacking with errors at almost every step. Some errors in problem solving showed by FI and FD subjects, so for further research need to analyse errors and the other cognitive style.